Optimized detection of caspase-6 activation in a murine inflammation model to inform neurodegenerative disease therapies - Irina Sagarbarria; Jamin Seo; Andrew J. Smith; Elena M. Vazey; Kimberly D. Tremblay; Jesse Mager; Jeanne A. Hardy (PLoS ONE, 2026)
Caspase-6 (casp-6), is a member of the apoptotic family of caspases (cysteine aspartic proteases) and has been shown to be involved in several neurodegenerative diseases, including Alzheimer’s disease. Drug discovery efforts have focused on specific inhibition of casp-6, and it is important that lead compounds demonstrate engagement and inhibition of the protease in vivo . A casp-6 overexpressing mouse model was reported, but is no longer available to the scientific community. We developed alternative means of activating casp-6 in commercially available mice as a platform to test potential casp-6 inhibitors. Lipopolysaccharides (LPS) from E. coli was used to stimulate an immunogenic response in WT C57BL/6NJ mice, which has been shown to activate the NLRP1 inflammasome, which activates casp-1 and subsequently, casp-6. Key tissues (brain, colon, and thymus) were sampled and evaluated for casp-6 activation by immunoblotting for both active casp-6 and a cleaved lamin A, a casp-6 substrate, and by directly measuring VEIDase activity in tissue lysates. Using in-house bred WT C57BL/6NJ mice, which had never been subjected to shipping, with a single intraperitoneal dose of LPS (5 mg/kg) and a 4-hour incubation, we observed robust casp-6 activation in the thymus. We also established VEIDase activity assays as a more reliable marker of casp-6 function than monitoring levels of casp-6 or cleaved substrates, and established the importance of using a non-immunogenic vehicle. We observed casp-6 activation in aged mice as a second useful model, which also further implicates casp-6 in age-related neurodegenerative pathways. These are new means to test the efficacy of casp-6 inhibitors using a simple in vivo assay that can robustly activate casp-6 in an easily accessible laboratory mouse strain. We foresee that these developments will drive drug discovery efforts aimed at identifying casp-6 inhibitors in various disease contexts, including neurodegeneration.